The Effect of Problem Based Learning (PBL) Learning Models on Mathematic Problem Solving Ability Students in Primary School - Agus Kistian; Verawati Verawati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model on the mathematics problem solving ability of students in 4th grade primary school Pasi Pinang. This research uses a quantitative approach, with the type of research is quasi experimental. The population in this study were all fourth grade students of primary school Pasi Pinang and the sampling technique in this study was selected by total sampling of two classes. The experimental class was treated with the Problem Based Learning (PBL) learning model and the control class was treated with the expository learning model. The instruments used consisted of a learning motivation questionnaire and a math problem solving ability test. Data analysis was carried out using two-way ANOVA. From the results of this study, it was obtained that the average result of the mathematics problem solving ability taught by the Problem Based Learning (PBL) learning model was 82.16 while the average result of the mathematics problem solving ability taught by the expository learning model was 71. , 36. So it can be concluded that the results of the mathematics problem solving ability of students who are taught with the Problem Based Learning (PBL) learning model are higher than students who are taught with the Expository learning model.